Balancing facets of workplace creativity: a holistic view of individual regulatory focus, idea generation paths and the interplay with the context. - Deuschel, Till Nicolas (IE University, 2020)
This dissertation addresses challenges presented by increasingly complex creativity research. In three chapters, it aims to synthesise several complexities of workplace creativity, including the output, the processes and interaction with the context. The first chapter is theoretical and offers a model of why and how employees create solutions with differing facets of novelty and usefulness. It draws on regulatory focus theory to discuss and distinguish between individual differences in promotion and prevention focus and introduce three self-regulation paths in the creative process. Further, the theoretical model accounts for interacting factors at the contextual level—and distinguishes their effect on creativity based on the degree of alignment with an employee’s goal-orientation strategy. The second chapter is empirical and focuses on the core psychological processes preceding creative output. Its findings suggest that the impact of promotion focus on creativity is mainly on the novelty side of creativity, while prevention focus in itself has no relation to either creativity facet. The final study investigates when and how the organizational context boosts or hinders employee creativity. It argues that the match between an individual and his/her organization’s collective regulatory focus orientation influences the individual´s ability to explore or exploit ideas. In two studies, the chapter shows that the regulatory fit to the perceived and actual (collective) organizational regulatory focus influences an employee’s ability to become creative.  Together, the three chapters contribute to creativity literature in several ways. By offering a theoretical model of workplace creativity, articulating the emotional-cognitive processes, it answers the call for theoretical work that specifies how diverse antecedents jointly affect creativity. Second, by examining the manner in which the different regulatory foci of individuals affect novelty and usefulness, it offers a refined view of emerging research on workplace creativity comprised of two distinct dimensions. Finally, by offering an organisational framework to help understand the underlying mechanisms of the creative behavior of individuals in organizations, this dissertation contributes to future empirical research investigating the mechanisms of interacting factors.
Equilibrar las facetas de la creatividad en el lugar de trabajo: una visión holística del enfoque regulatorio individual, las vías de generación de ideas y la interacción con el contexto.
Keywords: Creativity; Workplace; Interacting factors; Psychological processes; Organizational context; Creatividad; Lugar de trabajo; Elementos de interacción; Procesos psicológicos; Contexto organizacional